Effective combination of nisin and sesamol against Listeria monocytogenes. (15th February 2023) - Wu, Mengjie; Dong, Qingli; Song, Xia; Xu, Li; Xia, Xuejuan; Aslam, Muhammad Zohaib; Ma, Yue; Qin, Xiaojie; Wang, Xiang; Liu, Yangtai; Xu, Biyao; Liu, Hong; et al.
Abstract: Nisin (NS) has been considered as a food preservative against Listeria monocytogenes, an important foodborne pathogen that causes serious public health problems. However, the effectiveness of NS is also affected due to its instability and resistance of L. monocytogenes to NS. Combining NS with other antimicrobial substances is an excellent strategy to improve the effect. Sesamol (SE) has been reported to have the ability to inhibit the growth of L. monocytogenes . Thus, in this study, based on the determination of the fractional inhibitory concentration indices, the in vitro synergistic antibacterial activity of NS and SE was confirmed using standard L. monocytogenes ATCC19112 and L. monocytogenes isolated from food and clinical sources. The inhibition of NS and SE combination on the growth of L. monocytogenes was higher than that of NS or SE alone in tryptic soy yeast extract broth (TSB-YE) and pasteurized milk. The changes and damages of the cell structure and the cell morphology in the combination group were more significant than those in the single use of NS or SE. These results indicate that the combined application of NS and SE may be a promising alternative to NS for controlling the contamination of L. monocytogenes in food. Highlights: Nisin and sesamol combination showed synergistic effect against Listeria monocytogenes. Nisin and sesamol combination inhibited the growth of L. monocytogenes in milk. Nisin and sesamol combination disturbed function and morphology of L. monocytogenes cell membrane.